Preparation and Preliminary Biological Evaluation of Novel 99mTc-Labelled Thymidine Analogs as Tumor Imaging Agents - Jiankang Zhang; Cheng Tan; Chunxiong Lu; Quanfu Jiang; Jie Tang (Molecules, 2012)
Two kinds of novel thymidine derivatives, N-thymidine-yl-N′-methyl-N′-{N′′-[2-sulfanyl-(ethylamino)acetyl]-2-aminoethylsulfanyl-1-hexanamide}-ethanediamine (TMHEA) and N-thymidine-yl-N′-methyl-N′-{N′′-[2-sulfanyl-(ethylamino)acetyl]-2-aminoethylsulfanyl-1-hexanamide}-hexanediamine (TMHHA) were prepared and successfully labeled with 99mTc in high labeling yields. The in vitro stability and in vivo biodistribution of 99mTc-TMHEA and 99mTc-TMHHA were investigated and compared. The biodistribution studies indicate that the radiotracer 99mTc-TMHEA displays selective tumor uptake, suggesting it is a potential tumor imaging agent.